A Need Analysis of Interactive PowerPoint English Learning Media for Vocational Students - Nurul Isma Amalia Diko; Harni Jusuf; Nur Wahidah Thayib Pido; Jhems Richard Hasan; Nurwati Andi (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aimed to analyze students’ needs for interactive PowerPoint-based English learning media in the accounting expertise program at SMK Negeri 1 Limboto. The research employed a descriptive design within the Analysis stage of the ADDIE-based Research and Development (R&D) model, focusing on needs analysis grounded in English for Specific Purposes (ESP). The participants consisted of 15 tenth-grade students and one English teacher. Data were collected through questionnaires and semi-structured interviews and analyzed using descriptive statistics and qualitative thematic analysis. The results indicated that students showed a strong preference for interactive and multimedia-based learning media. Approximately 80% of students agreed that interactive media supports independent learning and time efficiency, while 73.3% reported increased activeness when using features such as videos, quizzes, and animations. In addition, 85% of students preferred visual and audiovisual media over text-based materials. The findings also revealed that most students experienced difficulties in speaking and writing and required learning media that integrates four language skills. These findings suggest that the development of interactive, contextual, and technology-based learning media is essential to enhance student engagement and support vocational English learning.